2008
DOI: 10.1086/591781
|View full text |Cite
|
Sign up to set email alerts
|

Mergers of Black Holes in the Galactic Center

Abstract: We present the results of three-body simulations focused on understanding the fates of intermediate-mass black holes (IBHs) that drift within the central 0.5 pc of the Galaxy. In particular, we modeled the interactions between pairs of 4000 M black holes as they orbit a central black hole (CBH ) of mass 4 ; 10 6 M . The simulations performed assume a Schwarzschild geometry and account for Chandrasekhar dynamical friction as well as acceleration resulting from energy lost due to gravitational radiation. We foun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…More recently, Koch and Hansen [15] explored additional effects, such as the interactions of IMBHs with themselves around an SMBH, assuming that the full coalescence process takes longer than the time needed for new clusters and IMBHs to sink to the center. They found that such encounters tend to eject one IMBH (although slowly, so that it will sink back in), and leave the other in an eccentric orbit that decays readily by emission of gravitational radiation.…”
Section: Imbh-smbh Mergersmentioning
confidence: 99%
“…More recently, Koch and Hansen [15] explored additional effects, such as the interactions of IMBHs with themselves around an SMBH, assuming that the full coalescence process takes longer than the time needed for new clusters and IMBHs to sink to the center. They found that such encounters tend to eject one IMBH (although slowly, so that it will sink back in), and leave the other in an eccentric orbit that decays readily by emission of gravitational radiation.…”
Section: Imbh-smbh Mergersmentioning
confidence: 99%